2020
DOI: 10.1111/cup.13908
|View full text |Cite
|
Sign up to set email alerts
|

Toker cell hyperplasia in Zuska disease: A tricky association

Abstract: Toker cells (TCs) are sometimes present in the nipple epidermis as oval cells with pale cytoplasm and roundish nuclei. In most cases, TCs may be easily distinguished from cancerous cells of Paget disease of the nipple (PCs). Especially in TC hyperplasia, in which mild-to-moderate atypia may be present, it may be challenging to distinguish between TCs and PCs. The combination of chronic inflammatory changes in the nipple, in the context of Zuska disease, and TC hyperplasia, may easily lead to an erroneous diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…19 Both Toker cell hyperplasia and EMPD will be positive for CK7, but the former is negative for Her-2/neu with low Ki-67 proliferation. 20 Determining a prognosis for collision tumors can be difficult because the aggressiveness of these lesions is unclear. Some have suggested that the less aggressive malignancy restricts the invasion of the more aggressive one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Both Toker cell hyperplasia and EMPD will be positive for CK7, but the former is negative for Her-2/neu with low Ki-67 proliferation. 20 Determining a prognosis for collision tumors can be difficult because the aggressiveness of these lesions is unclear. Some have suggested that the less aggressive malignancy restricts the invasion of the more aggressive one.…”
Section: Discussionmentioning
confidence: 99%
“…19 Both Toker cell hyperplasia and EMPD will be positive for CK7, but the former is negative for Her-2/neu with low Ki-67 proliferation. 20…”
Section: Discussionmentioning
confidence: 99%
“…Toker cell hyperplasia in the epidermis overlying SMOLD has recently been described. The authors suggested that inflammation may trigger the proliferation of Toker cells, 23 but this hypothesis requires further validation.…”
Section: Squamous Metaplasia Of the Lactiferous Duct (Smold)mentioning
confidence: 99%